2017
DOI: 10.1155/2017/5849173
|View full text |Cite
|
Sign up to set email alerts
|

Dental Abnormalities in Pituitary Dwarfism: A Case Report and Review of the Literature

Abstract: Hypopituitarism is a disorder caused by a reduced level of trophic hormones that may be consequent on different destructive processes. The clinical manifestations depend on the type of hormone involved. A deficiency of growth hormone (GH) in children causes the lack of growth known as pituitary dwarfism. The case is reported of a patient with pituitary dwarfism, multiple dental anomalies, functional prosthetic problems, and a revision of the literature. She was subjected to prosthetic rehabilitation without su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Hence, we thought that pituitary dwarfism has increased mortality compared to the normal population in surgery. Franco et al demonstrated that pituitary dwarfism there may be various anomalies of the dental apparatus, from the morphological profile and in terms of development (7). Patients with dwarfism due to various reasons need to be more cautious during anesthesia, and for patients with pituitary dwarfism, most people have a proportionately smaller airway without anatomic abnormalities (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we thought that pituitary dwarfism has increased mortality compared to the normal population in surgery. Franco et al demonstrated that pituitary dwarfism there may be various anomalies of the dental apparatus, from the morphological profile and in terms of development (7). Patients with dwarfism due to various reasons need to be more cautious during anesthesia, and for patients with pituitary dwarfism, most people have a proportionately smaller airway without anatomic abnormalities (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…The mutant protein misfolds and exerts a dominant negative effect through disruption of the trafficking and stability of wild-type GH1 (19,20), resulting in pituitary dwarfism. Orofacial anomalies are common in growth hormone deficiencies and include underdevelopment of the maxilla and mandible, delays in tooth eruption, and tooth agenesis or malposition (21,22). FTSJ3 has not been previously described as having a role in canine body size, although genome-wide studies have associated the locus with various height-( 23) and weight-related phenotypes in other species, including humans (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The possibly causes of dwarfism are the insufficient of growth hormone and genetic complication. Persons with pituitary dwarfism caused by deficient growth hormone and persons with achondroplasia caused by gene mutation that induce abnormalities dental formation such as abnormal tooth size and shape, crowded and impaction teeth with high risk of dental carries and periodontitis (Ferrante, Blasi, Crippa, & Angiero, 2017).…”
Section: The Persons With Physical Disabilitiesmentioning
confidence: 99%